Optical CDMA system parameters limitations for AND subtraction detection scheme under enhanced double weight (EDW) code based on simulation experiment - Hmud, Ihssan Sh.; Hasoon, Feras N.; Shaari, Sahbudin (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
The work in this paper is a simulation experiment performed by a computer program to determine the OCDMA system parameters limitations. The system was built up with LED light source in the transmitter with filters to construct the code where the receiver is constructed based on AND-subtraction detection scheme. The system was designed to be compatible with the enhanced double weight (EDW) code, passive optical network (PON), P2P network connection and fiber to the home (FTTH) topology. Five system parameters were considered in this work: the number of users, the transmission distance, the bitrate, the chip spacing and the transmitted power. Optisys 6.0 software program was used as a simulator; the simulator considered the entire practical effects in the system, like nonlinearities, attenuation in the fiber and dispersion. This paper shows that for sufficient system performance parameters (BER ≤ 1×10–9, Q ≥ 6) the system can stand for the maximum number of 3 users, the maximum distance of 21 km and the minimum chip spacing of 0.2. The system also shows that it cannot work for any number of users or any distance without the amplifier.
Optica Applicata, Vol. 40, 2010, nr 3, s. 669-676
Keywords: optyka; optical code division multiple access (OCDMA)